Occupational Stress and Mental Health Relationship in Nurses - Hosseini, zahra; Hazavehei, mohammad mahdi; Imanzad, masoumeh; Ghanbarnezhad, amin; Gharlipour, Zabihollah (Advances in Nursing & Midwifery, 2014)
Abstract Background and aim: Nursing is an stressful profession and nurses are often confronted with various stressors in their work environment. Job stress may have harmful effects on an individual’s physical and mental health and decrease quality of nursing care. The purpose of this study was to determine the relationship between job stress and mental health of nurses. Material and Methods: A cross-sectional design was used for the study. The sample of the study consisted of 237 nurses who were selected randomly from teaching hospitals in Hamadan, Iran. Data were collected by the nurses stress scale ( NSS) and GHQ-28. The validity of instruments was assured by a panel of experts. Cronbach’s alpha coefficient was computed to assess the reliability of instruments. The reliability coefficient was 0.93 for the nursing stress scale and 0.82 for the General Health Questionnaire. Data were analyzed using the SPSS-13. The relationship between job stress and mental health was investigated by calculating Spearman’s correlation coefficients and χ2. Results The majority of nurses reported high levels of job stress. There was a significant relation between sex and number of night shifts with job stress. Psychological problems were seen in 42.9% of hospital nurses. There was a significant correlation between job stress and general health scores. Conclusion: This study showed more than one third of the participants experienced high levels of job stress and mental disorders.There was significant relationship between job stress and mental health. It is recommended to reduce stress and mental health problems by stress management training Keywords: Stress, Mental health, Occupational stress. Job stress Nurses REFERENCES Abbaszadeh F. (2003); [ Health Global report2001,mental health: new precieve: new desire. Tehran. Avesina Catural Institution 30-33 (persian). Abdi H. (1994); [Assessing of stress in work please and relationship between stress and occupational burnout among intensive care unit nurses in Yazd]. MSc dissertation, Shahid Beheshti University of Medical Sciences, school of nursing, Tehran (persian). Afshari A, E. H., Mohadesi H. (2003); [ Assessing of mental health in new students in Orumie university]. journal of nursing and midwifery, 1(1) 34-39 (persian). Ahmadi F. (2003); Job stress in terms of nursing . Conference Proceedings of Occupational hazards among health staff, 17 (persian). Arian A. (2001); Principle of Stress Management . translated by Abutalebi A. second ed, Nasle no andisg publication. Tehran (persian). Bigdeli I, K. S. (2006); "Assessing stress factors in mental health among semnan nurses", Journal of koomesh , 8(2) 21-25 (persian). Decker FH. (1997); "Occupational and non occupational factors in job satisfaction and psychological distress among nurses", Journal of Research in Nursing and Health 20(5) 453-464. Depew CL, G. M., Yooder LH, Goodwin CW. (1999); "The relationship of burnout, stress, and hardiness in nurses in a military medical center: a replicated descriptive study", Journal of Burn Care Rehabil , 20(6) 515-522. Devries MW. (2003); "Stress, work and mental health: a global perspective", Acta Neuropsychiatrica 15 (1) 44-53. Douglas M. (1996); "The work of auxillary nurses in Mexico stressor satisfiers and coping strategies", International Journal Studies . 33(5) 495-505. Elizabeth MA. (2006); "A pilot study quantifting Filipino nurses perception of stress", Jornal of Health Promotion . 4(4) 88-95. Fagin L, B. D., Bartlett H, Leary J, Carson J. (1995); "The Claybury community psychiatric nurses stress study: Is it more stressful to work in hospital or the community?", Journal of Advanced Nursing , 22(2), pp. 347-358. Fathi M. (2004); "Assessing of Stress amongntensive care unit nurses", Journal of Kordestan university of medical sciences , 7(4) 53-62 (persian). Greenied S, J. P., Roger H. (2001); "The anxieties of male and female medical students on cosmmencing clinical studies: The role of gender", Education for Health ,14(1), pp.718-730. Haghighi J, A. E., Rahimi AS, Salmaninia L. (1999); "Relationship between persistence and mental health in male under graduate students", J ournal of Psychological Science of Ahvaz University , 6(3) 10-18 (persian). Hashemzade I, O. M., Bahrebardar MJ. (2000); "Relationship between job stress and psychological health in Shiraz university staff", Journal of Iran Psychiatry and Psychology (think and behavior), 6(2-3) 21-25 (persian). Khaghanizadeh M, E. A., Siratynayer M, Rahmani M,. (2008); "Relation between job stress and quality of work life among nurses in arm force hospitals", Journal of Medical Military , 10(3), pp. 175-184 (persian). Koshan M, V. S. (2007); Nursing psrchological of mental health. 3rd ed. andisheh rafie publication. Tehran, (persian) Lee I, W. H. (2002); "Occupational stress and related factors in public health nurses", The Journal of Nursing Research . 10(4) 253-260. Margolis BL. (1974); "Job stress:an unlisted occupational hazard", Journal of Occupational Medicine .16(1) 659-661. Martin SH. (1991); Mental stress]. Translated by Boloorchi P. , pasioang publication. Tehran.(persian). Milanifar B. (2003); Psychological Health , 3rd ed, Ghomes publication,Tehran, (persian). Molazem Z, M. S., Karimi Z, Bagheri GH. (2005); "Assessing of job stress factors and the score of stress them from sight of nurses in Kohkilooyeh Boyrahmad university of medical sciences hospitals", Journal of Armaghan Danesh , 10(3), 27-39 (persian). Najafi M, S. K., Foroozbakhsh F. (2001); "Relationship between Burnout and mental health among Research Center staff and Isfahan Nuclear fuel", Journal of Shahre Kord University of Medical Sciences , 2(2), 34-41 (persian). Noorbala A, M. K., Bagheri Yazdi SA, Yasemi MT. (2002); "Assessing of mental health among individuals higher than 15 years old, Republic Islamic of Iran’, Journal of Hakim , 5(1) 1-10 (persian). Palahang H, N. M., Baraheni MT, Shahmohammadi D. (1996); "Assessing of mental disorder epidemiology in Kashan", Journal of Think and Behavior , 2(4) 33-42 (persian). Payameni SH. (2002); "Stressors and adaptive methods in Khoramabad educational hospital nurses", Journal of Yaft-E , 9, 49-52 (persian). Rabinz S. (1995); Organizational Behavior Management , translated by Parsaeeian A, Aarabi M., Business study and research institution.Tehran( Persian). Rezaei N, B. N., Najafyarandi A, Hosseini F. (2006); "Relation between job stress and social support aming Nurses", Journal of Iran Nursing , 19(46 ) 21-32 (persian). Shamloo S. (2003); Psychological Health , 5th ed. Roshd publication,Tehran, (persian). Stura B. (1998); Stress:Civilization New Disease , translated by Dadsetan P, roshd publication.Tehran (Persian). Yaghubiniya F. (2001); "Relationship between Self-esteem and Burnout in nurses", Master’s Thesis Nursing , Mashhad university of medical sciences, (persian). Yang MS, P. S., Yang MJ. (2004); "Job strain and minor psychiatric morbidity among hospital nurses in southern Taiwan", Psychiatry and Clinical Neuroscience , 58 (6)636-641.